The Influence of Chatgpt Usage and Reading Literacy on the Learning Interest of Business Education Students of the 2022 Faculty of Economics, State University of Medan - Amimi, Fifin Sajdah; Saragih, Lenti Susanna (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the effect of using ChatGPT and reading literacy on the learning interest of Business Education students of the 2022 Stambuk Faculty of Economics, State University of Medan. The research method used is ex post facto with 63 students as research subjects. Data were collected through a questionnaire that measured the use of ChatGPT, reading literacy, and learning interest. The results of the analysis show that the use of ChatGPT has a positive effect on students' learning interest, with a t-count value of 6.447 and a significance of 0.000. In addition, reading literacy also has a positive effect, with a t-count value of 5.471 and a significance of 0.000. Simultaneously, the use of ChatGPT and reading literacy contributed 62.3% to students' learning interest. These findings indicate that the integration of technology in learning, such as ChatGPT, and increasing reading literacy can increase students' learning interest, which is important for developing more effective learning methods in the digital era.